A sidestep cut preparation strategy decreases the external load applied to the knee joint - Kimura, K.; Sakurai, S. (International Journal of Sport & Health Science, 2013)
In the present study, we aimed to investigate the joint moments applied to the cutting leg (CL) knee during the sidestep cut and during the final step before cutting (BC) at slow and fast speeds. Seven male university basketball players performed a sidestep cut 60° to the left, at fast (FAST, 80% of the maximum running speed) and slow (SLOW, 50% of the maximum running speed) speeds. The impulse of the mean anterior-posterior component of the ground reaction force and the peak external flexion moment of the BC knee during the FAST task were significantly larger than those during the SLOW task (0.54 ± 0.27 Ns·kg-1 vs. 0.12 ± 0.27 Ns·kg-1, P < 0.05, and 3.16 ± 0.64 Nm·kg-1 vs. 2.69 ± 0.42 Nm·kg-1, P < 0.05, respectively). The peak external valgus moment of the knee during the first half of the CL stance was also significantly larger during the FAST task than during the SLOW task (1.85 ± 0.56 Nm·kg-1 vs. 0.95 ± 0.57 Nm·kg-1, P < 0.05). The peak external flexion moment of the CL knee joint did not significantly differ between the FAST and SLOW tasks. The external load applied to the knee joint could be decreased by avoiding the combination of an external valgus moment and an internal extension moment of the CL knee. Therefore, BC deceleration during a high-speed sidestep cut is an effective strategy for decreasing the external load on the CL knee joint.